PENGARUH PENGGUNAAN MEDIA ULAR TANGGA TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS V di SDN 4 CAKRANEGARA - Juwita, Tita; Nurhasanah; Rachmatul Hidayati, Vivi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of using snakes and ladders media on the mathematical problem solving skills of fifth grade students at SDN 4 Cakranegara. This type of research is a quasi-experimental design type nonequivalent control group design. The sample of this study amounted to 42 students, consisting of class VA (22 students) as the experimental class and class VB (20 students) as the control class. Data collection methods are observation and test. The results of the research analysis concluded that between the experimental class and the control class there was a significant difference and an increase after treatment. In the experimental class, the average posttest score obtained by students was 84.90 while in the control class it was 65.60. In testing the hypothesis using an independent sample t test, the sig value was obtained. (2-tailed) (<0.001) ≤ 0.05 then rejected and accepted and the effect size test results obtained are 1,596 in the very large category. Thus it can be concluded that there is a significant effect on the use of snakes and ladders media on the mathematical problem solving ability of fifth grade students at SDN 4 Cakranegara.